A case study on the effects of Japan's immigration Act of 2005 to Filipino OPAs - Cruz, Bianca Vito (Animo Repository, 2010)
The study provided a concise view on the present situation of Filipino Overseas Performing Artists who went to Japan before the start of the implementation of Japans Immigration Control of 2005 which ruined the opportunities of these OPAs to go back to Japan. The study focused on how the OPAs managed to cope up with their lives in the present, now that they are not capable of going back to Japan. It also focused on the current situation of these OPAs and whether or not they were able to use the skills that they have managed to learn from working in Japan in order to sustain their everyday needs. There were nine respondents who were interviewed through a group discussion in order to supplement the study. These respondents used to work in Japan for a certain span of time but were unable to return due to the Revised Immigration Act which was passed by Japan in 2005 which only allows Performing Artist who were able to study for at least two years in college. This then became a problem for the OPAs since most of them were unable to study for college because of the financial problems that they had with their families. Although the opportunities of these OPAs to go back in Japan were hindered by the Immigration Control, some of these OPAs managed to cope up by opening up small businesses which enabled them to meet their everyday needs. And given that some of these OPAs were unable to find jobs where they ended up looking for some sidelines in order to gain income, they were still able to provide financial aid for their families and for themselves as well. The study did not only focus on the present status of these OPAs but also looked up on how the experiences of these OPAs were able to help them in their jobs at present. Although some of these OPAs are now working in local clubs, they were still able to learn from the experiences that they went through working as entertainers in Japan.